Peningkatan Kapasitas Produksi pada Mesin Bending LR 259 â€“ LR 260 di PT ABCD - Andriani, Andriani; Subuanda, Andri Putra (JURNAL TEKNIK INDUSTRI, 2021)
PT. ABCD is a company in the field of automotive spare parts for wheels 2 and 4, which produces braketubes for PT. TAM. This research contains how to increase the productivity of the bending process of the LR-259 machine and improve the quality of the LR-260 machine, especially the brake tube part. The problem that occurs is less than the maximum productivity. The method used in this research is PDCA analysis of conditions in the Production Group at PT. A B C D. By making improvements, making jig markings directly in 1 part and replacing the tertiary roll on the LR machineâ€“259 and LRâ€“260 engines. The results of the implementation of this improvement are able to reduce the number of man power from 6 to 5 people so as to reduce production costs. The existence of 1x jig marking that was carried out was able to reduce the cycle time from 56â€ to 3â€. So that the manufacture of 1 part which previously took 460 "is reduced to 407" with a fairly high productivity of 15.5 pcs/hour.